Gingerol Derivatives as 14α-demethylase Inhibitors: Design and Development of Natural, Safe Antifungals for Immune-compromised Patients - Sharma, Sweta; Yadav, Arpita (Letters in Drug Design & Discovery, 2020)
Background: Currently, clinically used drugs for internal fungal infections have severe side effects. Patients suffering from severe fungal infections and those at a constant risk of developing such infections require long-term administration of safe antifungals. Objective: This work deals with the design and development of safe, non-toxic antifungals derived from natural compounds for immune-compromised patients, such as HIV patients, who are at a constant risk of developing internal fungal infections. Methods: Molecular modeling, docking and molecular dynamics simulation studies were performed on the main constituents of ginger and their derivatives to study their capability to inhibit 14α- demethylase enzyme. Results: Ergosterol is the key component of the fungal cell membrane for its integrity and rigidity, synthesized from lanosterol catalyzed by 14α-demethylase enzyme. In our studies, it is determined that 6-gingerol, 6-paradol, 6-shogaol and their imidazole and triazole derivatives can inhibit the synthesis of ergosterol thus weakening the fungal cell membranes. The triazole derivative of 6-gingerol forms enhanced binding interactions with the active site residues of 14α-demethylase, carries an affinity for catalytically required cofactor heme and forms a stable complex with time without the probability of premature expulsion. Thus, this compound inhibits the formation of ergosterol leading to weakened fungal cell membranes and eventually death of fungal cells. Conclusion: The triazole derivative of 6-gingerol is recommended as a lead compound for the development of non-toxic antifungals.
Keywords: inhibition